Fashion and the Politics of the Body: Resistance among Young Feminist Activists in Yogyakarta - Bagus Ajy Waskyto Sugiyanto (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
This study will examine fashion as a form of resistance for women to actualize bodily autonomy. Women's lives within a patriarchal system shape the formation of a controlled discourse on women's fashion. This study interprets this control over women's fashion as a process of domesticating the body (docile bodies). Sandra Lee emphasizes that women's bodies are subject to discriminatory control. However, counter-discourse can change hegemonic discourse through the circulation of what Foucault calls